2017
DOI: 10.1038/bcj.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

Waldenstrom macroglobulinemia cells devoid of BTKC481S or CXCR4WHIM-like mutations acquire resistance to ibrutinib through upregulation of Bcl-2 and AKT resulting in vulnerability towards venetoclax or MK2206 treatment

Abstract: Although ibrutinib is highly effective in Waldenstrom macroglobulinemia (WM), no complete remissions in WM patients treated with ibrutinib have been reported to date. Moreover, ibrutinib-resistant disease is being steadily reported and is associated with dismal clinical outcome (overall survival of 2.9–3.1 months). To understand mechanisms of ibrutinib resistance in WM, we established ibrutinib-resistant in vitro models using validated WM cell lines. Characterization of these models revealed the absence of BTK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 53 publications
(79 reference statements)
3
33
0
1
Order By: Relevance
“…The WM cell lines BCWM.1 and RPCI‐WM1 and their isogenic ibrutinib‐resistant (IR) subclones BCWM.1/IR and RPCI‐WM1/IR were used in all experiments. Of note, IR subclones do not harbour BTK C481S or CXCR4 WHIM‐like mutations but are MYD88 L265P positive, as previously described (Paulus et al , ). In some experiments, CD19 + cells from a patient with relapsed and refractory disease and a confirmed diagnosis of WM (WM Patient 11) were used.…”
Section: Methodssupporting
confidence: 59%
See 2 more Smart Citations
“…The WM cell lines BCWM.1 and RPCI‐WM1 and their isogenic ibrutinib‐resistant (IR) subclones BCWM.1/IR and RPCI‐WM1/IR were used in all experiments. Of note, IR subclones do not harbour BTK C481S or CXCR4 WHIM‐like mutations but are MYD88 L265P positive, as previously described (Paulus et al , ). In some experiments, CD19 + cells from a patient with relapsed and refractory disease and a confirmed diagnosis of WM (WM Patient 11) were used.…”
Section: Methodssupporting
confidence: 59%
“…However, pBTK and PLCγ2 were reduced in RPCI‐WM1/IR cells (Fig K, L) and pERK1/2 was lower in BCWM.1/IR cells exposed to the ibrutinib + Dara combination, compared with single‐agent ibrutinib (Fig E, M). We and others have previously shown that IR cells preferentially utilize PI3K/AKT‐associated pathways via transcriptional reprogramming to safeguard against neoplastic growth and survival (Chiron et al , ; Paulus et al , ). Indeed, a significant decrease in pAKT and its downstream effector pS6/S6 was seen in RPCI‐WM1/IR cells treated with ibrutinib + Dara (Fig N, P), but this effect was not evident in BCWM.1/IR cells (Fig F, H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since macroglobulinemia cells highly express Bcl‐2 venetoclax is a logical therapy for this disorder …”
Section: Ibrutinibmentioning
confidence: 99%
“…A jelenleg WM-ben vizsgálat alatt álló szerek közül az everolimus, a copanlisib és a venetoclax más betegségekben már törzskönyve-zett, így indikáción túl WM-ben történő alkalmazásuk indokolt lehet [5,50]. Elesett általános állapotú, idős betegek palliatív kezelésére a plazmaferézissel kombinált alkilezőszer-monoterápia jó választás lehet.…”
Section: A Relabált Betegek Kezeléseunclassified